Costume at the National Theatre (Oberon Books, Ltd, 2019)
The National Theatre's Costume department is one of the theatre's largest departments. Their skilled practitioners work in a number of areas including tailoring, dyeing, costume props, costume production and maintenance to produce over 10,000 costume elements every year, transforming a designer's vision for a production into vibrant reality. Accompanying the National Theatre's showcase Costume exhibition from October 2019 to June 2020, Costume at the National Theatre is a lavish large-format photographic book featuring the extraordinary work of the Costume department, that will appeal to fans of theatre, costume and fashion.